Mindfulness training to improve the psychological well-being of school counselors - Krismona, Elwas Berdha (Program Studi bimbingan Konseling PPs UNM Makassar, 2024)
The study aims to examine the feasibility of mindfulness training in improving the psychological well-being of school counselors in vocational high schools in Bandung City. The research employed a quantitative approach with a quasi-experimental method using a non-equivalent pre-test – post-test control group design. The study involved 10 school counselors from vocational high schools in Bandung City, with various levels of psychological well-being: low, medium, and high. The teachers in the experimental group received mindfulness training, while those in the control group only received materials related to psychological well-being and mindfulness through a WhatsApp group. The analysis results using the Mann-Whitney test yielded a significance value of 0.009, indicating that mindfulness training is deemed feasible as an effort to improve the psychological well-being of school counselors.